THE EFFECT OF SAFETY AND HEALTHY , WORK LIFE BALANCE , AND JOB SATISFACTION ON EMPLOYEE PRODUCTIVITY AT PKS KOPERASI PRIMA JASA HAPPY COUNTRY - Ahdi Zikri; Likdanawati; Risna Dewi; Rahmaniar; Frengki Putra Ramansyah (RADJA PUBLIKA, 2026)
This study aims to analyze the impact of safety and healthy , Work Life Balance and job satisfaction on employee productivity. Researchers used quantitative methods, the sample in this study were all employees (saturated sample) of 106 respondents, Data were collected through questionnaires compiled based on the indicators of each variable and analyzed using multiple linear regression analysis with SPSS version 26. Hypothesis testing was carried out through the t test to determine the partial effect of each independent variable on employee productivity. The results showed that the Safety and healthy variable (X1 ) had a significance value of 0.05 (0.842> 0.05). In addition, the calculated t value was -0.200 <t table 1.983 (-0.200 <1.983). Partially, safety and healthy had a positive and significant effect on employee productivity. And Work Life Balance had a positive value of 0, with a calculated t value of 5.840> T table 1.983 and a significant value of 0.000 <0.05. Thus, it has a positive and significant impact on employee productivity. Furthermore, job satisfaction has a value of 0.578 with a calculated T value. 9.169 > T table 1.983 and significant value 0.000 < 0.05. has a positive and significant partial effect on Employee Productivity. Based on the results of this study, it is recommended that PKS Koperasi Prima Jasa Rantau Selamat pay more attention to the implementation of occupational safety and health programs, create policies that support Work Life Balance , and increase employee job satisfaction in order to increase productivity sustainably.